Pengembangan kecerdasan spiritual dan emosional melalui kegiatan keagamaan di SDIT Al-Yasmin 2 Bogor - Rihaadah, Faadiyah; Fahri, Muhammad; Andestend (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2025)
This research aims to determine efforts to develop spiritual intelligence and emotional intelligence through religious activity programs at SDIT AL-YASMIN 2, to find out what factors inhibit and support the development of spiritual intelligence and emotional intelligence through religious activity programs at SDIT AL-YASMIN 2 This research method uses qualitative methods with data collection techniques through observation, interviews and documentation. The results of the research show that religious activities carried out, such as congregational prayers, reading and writing the Qur'an, tahfizh Al-Qur'an, religious studies, and social religious activities, support the application of indicators of spiritual intelligence according to Dadang Hawari, faith and devotion to Allah. , maintaining trust and not lying, respecting time, having compassion for others and emotional intelligence according to Daniel Goleman, such as recognizing one's own emotions, managing emotions, motivating oneself, increasing empathy, and building harmonious relationships with the environment. By integrating religious education into daily activities, the school has succeeded in creating an atmosphere that supports the development of students' spiritual intelligence and emotional intelligence through religious activities. Abstrak Penelitian ini bertujuan untuk mengetahui upaya pengembangan kecerdasan spiritual dan kecerdasan emosional melalui program kegiatan keagamaan di SDIT AL- YASMIN 2, untuk mengetahui faktor apa saja yang menjadi penghambat dan pendukung dari pengembangan kecerdasan spiritual dan kecerdasan emosional melalui program kegiatan keagamaan di SDIT AL- YASMIN 2. Pendekatan penelitian ini menggunakan metode kualitatif dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa kegiatan keagamaan yang dilaksanakan, seperti shalat berjamaah, baca tulis Al-Qur’an, tahfizh Al-Qur’an, kajian keagamaan, dan kegiatan sosial agama, mendukung penerapan indikator kecerdasan spiritual menurut Dadang Hawari, beriman dan bertakwa kepada Allah, menjaga amanah dan tidak berdusta, menghargai waktu, memiliki rasa kasih sayang antar sesama serta kecerdasan emosional menurut Daniel Goleman, seperti mengenali emosi sendiri, mengelola emosi, memotivasi diri, meningkatkan empati, serta membangun hubungan yang harmonis dengan lingkungan. Dengan integrasi pendidikan agama dalam kegiatan sehari-hari, sekolah berhasil menciptakan suasana yang mendukung pengembangan kecerdasan spiritual dan kecerdasan emosional siswa melalui kegiatan keagamaan.